1968
DOI: 10.1161/01.res.23.1.69
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Excitability of Atrioventricular Nodal Cells

Abstract: The electrical threshold of A-V nodal cells of isolated rabbit heart preparations was estimated by techniques which permitted stimulation and recording through the same micropipette. Cells within the node were significantly less excitable than adjacent atrial and ventricular tissues; thresholds exceeded 5 X 10~~° amp in some instances. Recovery of excitability was delayed well beyond repolarization; in cells of the midnodal region, "diastolic" threshold was not attained until 0.2 to 0.5 seconds after restorati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
58
2
2

Year Published

1974
1974
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(63 citation statements)
references
References 16 publications
1
58
2
2
Order By: Relevance
“…Another possibility is that the supernormal response would propagate slowly through partially refractory tissue, and would be blocked eventually because it would fall outside the window of supernormality of the more At first glance, our results seem to contradict the classical microelectrode studies of Merideth et al 5 These authors studied recovery of excitability in the isolated rabbit AV node but did not demonstrate supernormality during repolarization. Yet, it should be kept in mind that although Merideth et a15 constructed a recovery of excitability curve from the N region of the AV node, they limited their study to scanning the diastolic interval with intracellular stimuli; they did not attempt to determine whether these cells were excitable during the repolarization phase.…”
Section: Potential Limitationscontrasting
confidence: 89%
“…Another possibility is that the supernormal response would propagate slowly through partially refractory tissue, and would be blocked eventually because it would fall outside the window of supernormality of the more At first glance, our results seem to contradict the classical microelectrode studies of Merideth et al 5 These authors studied recovery of excitability in the isolated rabbit AV node but did not demonstrate supernormality during repolarization. Yet, it should be kept in mind that although Merideth et a15 constructed a recovery of excitability curve from the N region of the AV node, they limited their study to scanning the diastolic interval with intracellular stimuli; they did not attempt to determine whether these cells were excitable during the repolarization phase.…”
Section: Potential Limitationscontrasting
confidence: 89%
“…This mechanism would therefore depend on N ceUs becoming inexcitable at short cycle lengths. It has indeed been shown that in N ceUs recovery of excitability occurs at a later time than completion of repolarization (125). This delayed recovery of excitability may be crucial in explaining failure of A Vnodal conduction of premature or successive rapid impulses.…”
Section: A Decremental Conduction Versus Electrotonic Transmissionmentioning
confidence: 99%
“…In only one study has the refractory period of A Vnodal cells been determined, by applying stimulating current through an intracellular microelectrode and, after a short latency, recording from the same microelectrode (125). It was indeed demonstrated that inthe N zone recovery of excitability was delayed and lagged behind full repolarization.…”
Section: Nature Of Lnward Gurrent In a Vnodal Gellsmentioning
confidence: 99%
“…Preto the expected responses of phase 4 depolarvious studies in rabbits showed that such rapid atrial ) those interventions. These results, together pacing most likely blocked in the N region of the AV previous results on recordings of diastolic node.8 9 Thus the pause after rapid atrial pacing and om the sinus node, ectopic atrial pacemakers, underdrive of the His bundle in figure 1 is most consisjunction, and the ventricles'-5 suggest that the tent with a pacemaker location in the N or AN region. slope recorded from the AV junction indeed However, the AN location (coronary sinus ostial loca-)hase 4 activity of the junction.…”
Section: Discussionmentioning
confidence: 66%